ROA Dan PBV Serta Pengaruhnya Terhadap Likuiditas Saham Perusahaan Real Estate Di Jakarta Islamic Index - Al Amiri Octadianto; Nisful Laila (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The This study aims to examine and analyze the influence of Return On Asset (ROA) and the Price to Book Value (PBV) towards on the liquidity stock of the real estate companies in JII. ROA shows the ability of the companies with the assets that work in it to gain the net profit, shows in percentage. PBV is the ratio of stock in the market compare with the book value of the company.This study used quantitative. The samples used in this study are the real estate companies registered in JII during 2013-2015 period. This study selects four companies as the sample. This study used multiple linear regression analysis tests. The test results of multiple regression analysis with 5% significance level, shows: (1) ROA and PBV partially has no significant effect on liquidity stock (2) ROA and PBV simultaneously has significant effect on liquidity stock.